Ethnobotanical study of Penchalakona forest area of Nellore District, Andhra Pradesh, India - N. Savithramma; M. Linga Rao; P. Yugandhar; R. Hari Babu (International Journal of Phytomedicine, 2012)
An ethno botanical survey was undertaken to collect information from yanadi tribe of penchalakona forest area, Rapur mandal, Nellore district, Andhra Pradesh, India. The indigenous knowledge of traditional healers of this ethnic group has been disappearing due to lack of ancestors as well as followers. Only few people are practicing with little knowledge which was transmitted orally from their elders. The native plants used for medicinal purposes by few people were collected through questionnaire and personally interviewed during field trips. An aboriginal tribe called “Yanadi”, of this area has authentic information on medicinal values of different plant species. Yanadi tribal community being drifted from their natural way of life due to agro rural development activities, a few aged persons are still able to furnish very little traditional ethno botanical data and continue to depend on medicinal plants atleast for the treatment of primary healthcare. Because the area is located near the forest and 70 Kms from Nellore town.The study revealed that, the Yanadi tribe used 20 plants species belonging to 20 families to treat various diseases like worm infestations, scorpion stinge, headache, body pains, fevers, swelling of foots, skin diseases, heart diseases, stomach ulcers, diuretic, dysentery, snake bites, nerve disorders, rheumatic pains, antiseptic, helmentic disease, diabetes, cold and dental problems.These plants represents the major source for the pharmaceutical industries in view of their raw material. The information requires validation for further clinical usage.